Chemical and Sensory Characteristics of Chicken and Purple Yam (Dioscorea alata L.) Snack Bars with Added Seaweed - Feby Salsabilla; Dedin F. Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Snack bars are a type of ready-to-eat food product that is convenient, compact, and suitable as a snack. Snack bars are generally made from plant-based ingredients such as grains, nuts, and dried fruit, while the use of animal protein sources remains relatively limited. In addition, purple yam can be used as a source of carbohydrates that is rich in fiber and contains antioxidants beneficial to health. The production of snack bars requires a binding agent, one of which is seaweed containing carrageenan, which serves to improve texture quality, making the product more compact. This study aims to determine the effect of the proportions of purple yam flour and dried chicken meat, with the addition of seaweed, on the physicochemical and organoleptic characteristics of snack bars. This study employed a Completely Randomized Design (CRD) with two factors: Factor I—the ratio of purple yam flour to dried chicken meat (55:45, 40:60, 25:75)—and Factor II—seaweed content (20%, 30%, 40%). The data obtained were analyzed using ANOVA, followed by a DMRT post-hoc test at the 5% significance level. The optimal treatment was found in the treatment with a 45:55 ratio of purple yam flour to dried chicken meat and 40% seaweed. This treatment resulted in snack bars with a moisture content of 14.58%, ash content of 4.4%, fat content of 16.12%, protein content of 28.17%, carbohydrate content of 35.99%, and dietary fiber 8.74%. The hedonic organoleptic characteristics were as follows: color 3.5; aroma 4.0; texture 3.7; and flavor 3.9. The snack bars produced are expected to serve as a highly nutritious, functional snack alternative made from local food ingredients. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production